Pediatric NMDAR encephalitis: A single center observation study with a closer look at movement disorders. (March 2018) - Granata, Tiziana; Matricardi, Sara; Ragona, Francesca; Freri, Elena; Zibordi, Federica; Andreetta, Francesca; Binelli, Simona; Nardocci, Nardo
Abstract: Anti-N-Methyl-d -aspartate-receptor (NMDAR) encephalitis is the most frequent autoimmune encephalitis in pediatric age. This retrospective observational study was aimed at describing the clinical characteristics of the disease in a cohort of children and teenagers. Eighteen patients (10 females and 8 males), with a median age of 12.4 years at symptom onset were enrolled. The clinical presentation of the disease was marked by neurological manifestations in 13 patients and by severe psychiatric and behavioral symptoms in 5. The symptoms at onset varied according to the age: all the children presented with prominent neurological symptoms, whereas psychiatric symptoms were prominent in teenagers. Regardless the age, movement disorders (MDs) were distinctive symptoms during the acute stage of the disease. Several MDs might coexist in a given patient, and persist during sleep. The complexity, and the oddness of MDs often challenged their definition and the differential diagnosis with psychiatric manifestations and epileptic seizures. Stereotyped motor phenomena were the most typical MDs, and were recorded in all patients. Among them, perseveration, reproduction of acquired complex motor activities, and orofacial dyskinesia were the most distinctive features. In children, hyperkinetic MDs dominate; in teenagers, by contrast, a constellation of symptoms consistent with catatonia was the most frequent syndrome observed. The management of the several symptoms requires their accurate recognition, definition and assessment, and the knowledge of the potential side effects of antiepileptic and psychotropic drugs which could either mimic or worsen symptoms of encephalitis. Highlights: In anti-NMDAR-encephalitis, several MDs may coexist in a given patient, and persist during sleep. Young children mostly feature hyperkinetic MDs with chorea, dystonia and stereotypes. Teenagers mostly feature with a constellation of symptoms consistent with catatonia. The complexity, and the oddness of MDs often challenge their definition. The differential diagnosis is with psychosis and epilepsy and may require video-EEG.